2019
DOI: 10.1111/ina.12574
|View full text |Cite
|
Sign up to set email alerts
|

Parental worry about indoor air quality and student symptom reporting in primary schools with or without indoor air quality problems

Abstract: Poor indoor air quality (IAQ) in schools is related to increased symptom reporting in students. We investigated whether parental worry about school IAQ influences this association. Data came from survey collected from five Finnish primary schools with observed IAQ problems and five control schools. Parents (n = 1868) of primary school students reported worry about IAQ in schools and symptoms of their children. Associations between observed IAQ problems, worry, and five symptom scores (ie, respiratory, lower re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 32 publications
2
17
0
Order By: Relevance
“…Among psychosocial factors, worry about school IEQ was consistently associated with higher respiratory symptom reporting in all three main samples, as well as in the combined sample of parent-child pairs where children reported psychosocial factors themselves and parents reported symptoms for their children. In line with previous studies 26 showing that parents worried about school IEQ reported their children having symptoms more often than non-worried parents, we found that also pupils who were worried about school IEQ tend to report more respiratory symptoms independently of their individual and allergic characteristics, other psychosocial factors, and school IEQ. One possible explanation for this is that worries about health threats may change the way people perceive and interpret somatic information.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Among psychosocial factors, worry about school IEQ was consistently associated with higher respiratory symptom reporting in all three main samples, as well as in the combined sample of parent-child pairs where children reported psychosocial factors themselves and parents reported symptoms for their children. In line with previous studies 26 showing that parents worried about school IEQ reported their children having symptoms more often than non-worried parents, we found that also pupils who were worried about school IEQ tend to report more respiratory symptoms independently of their individual and allergic characteristics, other psychosocial factors, and school IEQ. One possible explanation for this is that worries about health threats may change the way people perceive and interpret somatic information.…”
Section: Discussionsupporting
confidence: 92%
“…In schools with poor IEQ, parents who were worried about school IEQ reported more symptoms for their children than not worried parents. Although it has been suggested that worry might act as a potential explanatory variable on the pathway between school IEQ and symptom reporting, 26 we cannot eliminate the possibility that pupils experience more symptoms in schools with poor IEQ which in turn induces more worries. Also, findings in parental data should be interpreted with caution due to the low response rate of parents (less than 20%) and possible self-selection bias.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In addition, special attention should be given to open, respectful, and regular organizational communication [44]. IE problems raise concerns [45], and being worried may also affects people's well-being [46].…”
Section: Discussionmentioning
confidence: 99%